On new extensions of F-contraction with an application to integral inclusions - Kaddouri, H.; Işık H.; Beloul S. (Politechnica University of Bucharest, 2019)
The purpose of this study is to present some fixed point theorems by combining the contractions of Geraghty and Hardy-Rogers with F-contraction and ?-admissible concept in the setting of set-valued mappings under weaker conditions. We derive new fixed point results on a metric space endowed with a partial ordering/graph by using the results obtained herein. We give also an example and an application to support new theory. © 2019, Politechnica University of Bucharest. All rights reserved.
Keywords: F-contraction; Geraghty contraction; Hardy-Rogers contraction; Integral inclusion; Semi-lower continuous; ?-admissible